Talking While Signing: The Influence of Simultaneous Communication on the Spoken Language of Bimodal Bilinguals. - Rozen-Blay, Or; Novogrodsky, Rama; Degani, Tamar (Journal of Speech, Language & Hearing Research, 2022)
Purpose: This study aimed to examine how speech while sign (simultaneous communication [SimCom]) affects the spoken language of bimodal bilingual teachers and how individual differences in sign-language vocabulary knowledge, SimCom teaching experience, and the ability to perform speech under dual-task conditions explain the variability in SimCom performance. Method: Forty experienced teachers of deaf and hard of hearing students participated in a story narration task under different conditions. Speech rate, lexical richness, and syntactic complexity were measured and compared across speech-only versus SimCom conditions. Furthermore, participants’ score on a sign-language vocabulary test, their self-reported SimCom teaching experience, and their performance in a dual-task condition were taken as predictors of SimCom narration performance. Results: The findings revealed slower speech rate, lower lexical richness, and lower syntactic complexity in the SimCom condition compared with the speech only condition. Sign-language vocabulary score and SimCom teaching experience explained speech rate and lexical richness. Participant’s ability to speak under a dual-task condition did not modulate performance. Conclusions: The findings may suggest that the production of the less dominant (sign) language during SimCom entails inhibition of the dominant (spoken) language relative to the speech-only condition. At the same time, the findings are also compatible with the suggestion that SimCom serves as a unique complex communication unit that cannot be reduced to the combination of two languages.